Penerapan Metode Grey Relational Analysis (GRA) Dalam Pemilihan E-Commerce - Sanriomi Sintaro (Journal of Information Technology, Software Engineering and Computer Science, 2023)
The choice of an e-commerce platform is a critical decision that can affect the success of an online business. The selection of an e-commerce platform with a decision support system involves a careful and strategic process. This study aims to select e-commerce by applying the Gray Relational Analysis (GRA) method based on data obtained from similarweb websites based on the category of most visited marketplace websites. The ranking results were obtained for rank 1 with a final value of 0.2024 obtained by Shopee e-commerce, rank 2 with a final value of 0.1380 obtained by Tokopedia e-commerce, rank 3 with a final value of 0.0921 obtained by Lazada e-commerce.